2019
DOI: 10.1073/pnas.1900751116
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic viral attenuation through an ancestral apoptotic pathway

Abstract: The programmed release of apoptogenic proteins from mitochondria is a core event of apoptosis, although ancestral roles of this phenomenon are not known. In mammals, one such apoptogenic protein is Endonuclease G (EndoG), a conserved mitochondrial nuclease that fragments the DNA of dying cells. In this work, we show that budding yeast executes meiotically programmed mitochondrial release of an EndoG homolog, Nuc1, during sporulation. In contrast to EndoG’s ostensible pro-death function during apoptosis, Nuc1 m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
42
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 58 publications
(71 reference statements)
6
42
2
Order By: Relevance
“…This observation is consistent with the hypothesis that mitochondrially-released Nuc1 during yeast meiotic PCD accomplishes nucleosomal laddering, paralleling the role of mitochondrial membrane permeabilization in the release of apoptogenic proteins during mammalian PCD [9]. We recently confirmed that Nuc1 accumulates in the cytosol of meiotic cells in a developmentally programmed manner, supporting this model [10].…”
supporting
confidence: 89%
See 4 more Smart Citations
“…This observation is consistent with the hypothesis that mitochondrially-released Nuc1 during yeast meiotic PCD accomplishes nucleosomal laddering, paralleling the role of mitochondrial membrane permeabilization in the release of apoptogenic proteins during mammalian PCD [9]. We recently confirmed that Nuc1 accumulates in the cytosol of meiotic cells in a developmentally programmed manner, supporting this model [10].…”
supporting
confidence: 89%
“…Open questions remain concerning the mechanistic basis and developmental regulation of Nuc1's dual roles in viral attenuation and meiotic PCD. Although Nuc1 enzymatic activity is required for attenuation, there is only circumstantial evidence for direct attenuation of Killer by cytosolic Nuc1 [10]. Indeed, Liu and Dieckmann identified L-A attenuation by Nuc1 in vegetative haploid cells, whereas we did not detect Nuc1 in the cytosol of vegetative cells [16].…”
contrasting
confidence: 77%
See 3 more Smart Citations